Activation of Parabrachial Nucleus Glutamatergic Neurons Accelerates Reanimation from Sevoflurane Anesthesia in Mice. (January 2019) - Wang, Tian-Xiao; Xiong, Bo; Xu, Wei; Wei, Hao-Hua; Qu, Wei-Min; Hong, Zong-Yuan; Huang, Zhi-Li
Editor's Perspective: What We Already Know about This Topic: The parabrachial nucleus is a brainstem region involved in arousal. Brain regions involved in arousal regulate anesthetic induction and emergence. What This Article Tells Us That Is New: Using chemogenetic techniques, activation of parabrachial nucleus glutamatergic neurons prolonged anesthetic induction and hastened emergence in mice. Inhibition of these neurons provided opposite effects. Modulating the activity of arousal centers may provide an approach to controlling the duration of general anesthesia. Background: The parabrachial nucleus (PBN), which is a brainstem region containing glutamatergic neurons, is a key arousal nucleus. Injuries to the area often prevent patient reanimation. Some studies suggest that brain regions that control arousal and reanimation are a key part of the anesthesia recovery. Therefore, we hypothesize that the PBN may be involved in regulating emergence from anesthesia. Methods: We investigated the effects of specific activation or inhibition of PBN glutamatergic neurons on sevoflurane general anesthesia using the chemogenetic "designer receptors exclusively activated by designer drugs" approach. Optogenetic methods combined with polysomnographic recordings were used to explore the effects of transient activation of PBN glutamatergic neuron on sevoflurane anesthesia. Immunohistochemical techniques are employed to reveal the mechanism by which PBN regulated sevoflurane anesthesia. Results: Chemogenetic activation of PBN glutamatergic neurons by intraperitoneal injections of clozapine-N-oxide decreased emergence time (mean ± SD, control vs . clozapine-N-oxide, 55 ± 24 vs . 15 ± 9 s, P = 0.0002) caused by sevoflurane inhalation and prolonged induction time (70 ± 15 vs . 109 ± 38 s, n = 9, P = 0.012) as well as the ED50 of sevoflurane (1.48 vs . 1.60%, P = 0.0002), which was characterized by a rightward shift of the loss of righting reflex cumulative curve. In contrast, chemogenetic inhibition of PBN glutamatergic neurons slightly increased emergence time (56 ± 26 vs . 87 ± 26 s, n = 8, P = 0.034). Moreover, instantaneous activation of PBN glutamatergic neurons expressing channelrhodopsin-2 during steady-state general anesthesia with sevoflurane produced electroencephalogram evidence of cortical arousal. Immunohistochemical experiments showed that activation of PBN induced excitation of cortical and subcortical arousal nuclei during sevoflurane anesthesia. Conclusions: Activation of PBN glutamatergic neurons is helpful to accelerate the transition from general anesthesia to an arousal state, which may provide a new strategy in shortening the recovery time after sevoflurane anesthesia. Abstract : Using chemogenetic techniques, activation of parabrachial nucleus glutamatergic neurons prolonged anesthetic induction and hastened emergence in mice. Inhibition of these neurons provided opposite effects. Modulating the activity of arousal centers may provide an approach to controlling the duration of general anesthesia.